Extending the Unified Modelling Language to support visualisation of ontology models. (25th January 2008) - Yu, Changrui; Luo, Yan; Wang, Hongwei
Many features of UML are not generally available in most ontology languages. Meanwhile, ontology languages have some features that UML does not support. This paper focuses on extending UML to support visualisation of ontology models. First, this paper gives a brief review of ontology models and the many mature UML tools. Secondly, the paper identifies similarities and differences between UML and the ontology language DAML, elaborates on the key problems for UML representation of ontology, and analyses deficiencies of UML extension proposed by Baclawski. To reconcile these differences, we then propose a modest extension to UML infrastructure for the most problematic differences.